Pengaruh Peran Kepemimpinan dan Komunikasi Terhadap Kinerja Pegawai Pada Dinas Lingkungan Hidup Kota Bekasi - Ngulandoro, Anindityo Guruh; Fadili, Dadan Ahmad (Peneliti.net, 2024)
This study has the intent and purpose to analyze and test the Influence of the Role of Leadership and Communication on Employee Performance at the Bekasi City Environmental Service. This research uses quantitative methods with descriptive and verification analysis which has activities such as collecting, presenting, analyzing, and conducting a series of tests such as hypothesis testing, as well as making conclusions and suggestions. This study has a population of 349 Civil Servants (ASN) at the Bekasi City Environment Service and only 186 ASN samples were taken using the Taro Yamane method and non-probability sampling and using a purposive sampling method. The analysis used uses a Likert scale analysis technique and path analysis. Based on the research that has been done, this research can prove that the leadership role at the Bekasi City Environmental Service shows a value of 709 which is included in the